Enhanced accumulation of Cd in castor (Ricinus communis L) by soil-applied chelators. Issue 7 (2nd July 2016) - Chhajro, Muhammad Afzal; Rizwan, Muhammad Shahid; Guoyong, Huang; Jun, Zhu; Kubar, Kashif Ali; Hongqing, Hu
ABSTRACT: Phytoextraction has been identified as one of the most propitious methods of phytoremediation. This pot experiment were treated with varying amounts of (ethylenediamine triacetic acid) EDTA 3–15, (Nitriloacetic acid) NTA 3–10, (Ammonium citrate) NH4 citrate 10 – 25 mmol and one mg kg –1 Cd, filled with 5 kg soil. The addition of chelators significantly increased Cd concentration in soil and plant. The results showed that maximum Cd uptake was noted under root, shoot and leaf of castor plant tissue (2.26, 1.54, and 0.72 mg kg –1 ) under EDTA 15, NTA 10, and NH4 citrate 25 mmol treatments respectively, and in soil 1.08, 1.06 and 0.52 mg kg –1 pot –1 under NH4 citrate 25, NTA 10 and EDTA 15 mmol treatments respectively, as against to control (p < 0.05). Additions of chelators reduction biomass under the EDTA 15 mmol as compared to other treatments, However, Bioconcentration factor (BCF), translocation factor (TF) and remediation factor (RF) were significantly increased under EDTA 15 and NH4 citrate 25 mmol as against control. Our results demonstrated that castor plant proved satisfactory for phytoextraction on contaminated soil, and EDTA 15 and NH4 citrate 25 mmol had the affirmative effect on the Cd uptake in the artificial Cd-contaminated soil.